Study on the Rehabilitation Therapist Estimation Under Institutional Perspective by Applying the Workload Indicators of Staffing Needs in the Aging Context - Jing, Qi; Xing, Yang; Duan, Mingxue; Guo, Peiwu; Cai, Weiqin; Gao, Qianqian; Gao, Runguo; Ji, Lihong; Lu, Jun (Frontiers in Public Health, 2022)
Background: The need for rehabilitation therapy has increased dramatically with the ageing of the population, the prevalence of non-communicable diseases, and the increase in the number of disabilities. Rehabilitation therapists are crucial to provide high quality rehabilitation therapy; however, there is a significant shortage of these professionals in China. One of the effective strategies to address this challenge is using the norm of the workforce for rehabilitation therapy, which is an index for assessing the personnel required in a facility. This research aimed to create a rehabilitation therapist-required norm under institutional perspective in Shandong Province, China, based on the Workload Indicators of Staffing Needs (WISN) method, which was created by the World Health Organization (WHO) in 1998 to analyse staff utilisation at various levels of the health care system. Methods: We conducted descriptive and quantitative research from October to November 2020 in the rehabilitation department of a tertiary hospital in Weifang City, China. Focus groups, online interviews, and document reviews were conducted to gather data and calculations of the WISN method performed. Results: Admission assessment, pre-treatment evaluation, rehabilitation therapy, post-treatment evaluation, and health education for patients were identified as the main priority group activities. Interviews and analysis of documents summarised five factors related to rehabilitation therapists’ health service activities. In this study, the annual working time of each therapist was 1776 h per year. The WISN method calculations showed that the norm of rehabilitation therapists in this tertiary hospital was 23 therapists. As the department had 13 therapists, there was a shortage of 10 therapists based on the WISN calculation, with a ratio of 0.57, which represented the actual compared to the ideal number of therapists. Conclusion: Workload pressure was high for therapists in this tertiary hospital. This model revealed a demand for ten more therapists in the rehabilitation department. The WISN method can help hospital administrators in therapist workforce monitoring, including in regard to therapists. Therefore, the WISN method should be embraced as part of hospital human resource planning and recruitment strategies to meet increasing rehabilitation needs.